Strategy Development for Installing Children's Awareness of National Resilience as an Indonesian Geostrategy - Pranajati, Nindya Rachman; Ichsan, Ahmad Shofiyuddin (Lembaga Yasin AlSys, 2025)
The investment in making students aware of the geostrategy for national resilience in the educational space was immediately implemented because educational problems were becoming more worrying, and the best and most comprehensive solutions needed to be found as soon as possible. This research aimed to reveal the development of a strategy for cultivating awareness of national resilience in children as a geostrategy in Indonesia. Researchers used qualitative research methods with the type of library research through various documentation sources, both from scientific journals, books, websites, and other relevant information; meanwhile, in data analysis techniques, researchers use content analysis. The research results showed at least three awareness development strategies for children, including First, a strategy for cultivating children's awareness based on the values of Pancasila ​through the study of the first to the fifth principles. Second, the project system-based strategy for cultivating children's awareness through national holiday activities, heroism day activities, and collaborative activities with the surrounding environment. Third, the strategy for cultivating children's awareness is based on the value of integrating subjects in the educational curriculum through the integration of allied lessons, material on the dynamics of the reality of life, self-control, and social movements, and understanding the noble value of the nation's philosophy for life.